Optimization of recombinant vanadium-dependent haloperoxidase production from gracilaria changii - Ng, Shaunie May Qi (2015)
Vanadium-dependent haloperoxidases (VHPOs) belong to one of the three classes of haloperoxidases which can oxidize halogens including chloride (Cl-), bromide (Br-), and iodide (I-). Chemical halogenation of organic compounds typically requires harsh conditions. Hence, biohalogenation has gained increasing research interest. As vanadium-dependent haloperoxidases are enzymes that catalyze halogenation of organic compounds, they are very valuable due to their potential applications in various industries as well as their stability and tolerance for different conditions. This study aims to optimize the recombinant protein expression conditions, for potentially large scale production of vanadium-dependent bromoperoxidase 2 (GcVBPO2) that was previously isolated from Gracilaria changii. GcVBPO2 sequence in pET32a(+) was transformed into expression host Escherichia coli BL21(DE3) pLySs and induced at various temperatures. GcVBPO2 was found to be soluble when induced with 0.5mM Isopropyl β-D-1-thiogalactopyranoside (IPTG) for 16 hours in Luria-Bertani (LB) broth culture at 20°C. Purification of GcVBPO2 was performed using His-tag purification, and subsequently analysed with Western blot.